The Effect of Consumption of Mung Bean Extract on Increasing HB Levels of First Trimester Pregnant Women in the Working Area of Harapan Baru Health Center in 2021 - Naumi E.M; Jasmawati; Rivan Firdaus (PT FORMOSA CENDEKIA GLOBAL, 2022)
ased on Riskesdas data (2018), the prevalence of anemia during pregnancy, data obtained in 2011 from all Puskesmas in Samarinda obtained 18.86% of pregnancies suffering from anemia, data on the maternal mortality rate in Samarinda in 2015 as many as 76 per 100,000 live births experienced a significant increase This is significant when compared to the maternal mortality rate in 2014, which was 50 per 100,000 live births. To determine the effect of consuming mung bean extract on increasing Hb levels in first trimester pregnant women. The type of research used was quasi-experimental with pre-test and post-test approaches. The statistical test of paired samples t-test obtained a value of t = -12.41 and p = 0.001 (p <0.05) meaning that there was a significant effect of giving mung bean juice to increasing hemoglobin levels in Trimester I pregnant women at Harapan Baru Health Center.